1967
DOI: 10.1111/j.1432-1033.1967.tb19494.x
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Phosphoenolpyruvate in the Gluconeogenesis

Abstract: Livers of chick embryos a t different stages of incubation have been fractionated into mitochondrial and "soluble" fractions by centrifugation.The pyruvate carboxylase and phosphoenolpyruvate carboxykinase activities, which constitute the major pathway for the synthesis of phosphoenolpyruvate, have been measured in both preparations.The pyruvate carboxylase activity occurs only in the mitochondria and parallels the gluconeogenetic ability.The bulk of phosphoenolpyruvate carboxykinase activity appears in the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…They vary considerably in experimental design, but the enzymes showed maximum activities largely between E14 and E17 in some of these reports (Rinaudo, 1961;Ballard and Oliver, 1963;Felicioli et al, 1967). These results are consistent in tendency with our present data that the expressions of the enzymes had peaks mainly on E13 or E15 and declined thereafter (Fig.…”
Section: Liversupporting
confidence: 92%
See 2 more Smart Citations
“…They vary considerably in experimental design, but the enzymes showed maximum activities largely between E14 and E17 in some of these reports (Rinaudo, 1961;Ballard and Oliver, 1963;Felicioli et al, 1967). These results are consistent in tendency with our present data that the expressions of the enzymes had peaks mainly on E13 or E15 and declined thereafter (Fig.…”
Section: Liversupporting
confidence: 92%
“…Also, PEPCK-C gene expression in embryonic chicken liver was inducible by dexamethasone administration with a progressively decreasing responsiveness from E12 until E15 (McCaffrey and Hamilton, 1994). However, Felicioli et al (1967) reported that enzyme activity of PEPCK-C in the liver was very low between E13 and E21. Watford (1985) pointed out that, although PEPCK-C mRNA was considerably increased in the liver of adult chickens deprived of food, its enzyme activity remained very low.…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…In corporation of 14C-amino acids and 14CC>2 into glucose by liver slices from embryonic chicken is temporally associated with the ac tivity of the gluconeogenic enzymes pyruvate carboxylase, fructose 1,6-diphosphatase, glucose-6-phosphatase and PEPCK [6][7][8], Pre vious studies undertaken to determine the subcellular distribution of the two isozymes of PEPCK in the developing avian liver have, however, given divergent results. In one case [9] substantial amounts of only PEPCK-M activity were observed throughout embryonic development, whereas in another study a ra tio of mitochondrial to cytosolic enzyme ac tivity of approximately 70:30 was noted [10].…”
Section: Introductionmentioning
confidence: 99%
“…The maximal activity of both pyruvate carboxylase (EC 6.4.1.1.) and phosphoenol pyruvate carboxykinase (EC 4.1.1.32) occurs on day 17 (Nelson et al, 1966;Felicioli et al, 1967).…”
Section: Resultsmentioning
confidence: 98%